If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -36 = 3x Reorder the terms: -36 + 7x = 3x Solving -36 + 7x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -36 + 7x + -3x = 3x + -3x Combine like terms: 7x + -3x = 4x -36 + 4x = 3x + -3x Combine like terms: 3x + -3x = 0 -36 + 4x = 0 Add '36' to each side of the equation. -36 + 36 + 4x = 0 + 36 Combine like terms: -36 + 36 = 0 0 + 4x = 0 + 36 4x = 0 + 36 Combine like terms: 0 + 36 = 36 4x = 36 Divide each side by '4'. x = 9 Simplifying x = 9
| 10x+13=68-x | | 9y^2-12y+1=0 | | 3x+8=2x+20 | | 7(3x+4)=9x-12-x | | 2x+3+4x+2=11 | | 13x-(25+11x)=165-2(4x+10) | | 16x^2-13x=0 | | 5x+37=179 | | 12-3(2x+9)=15 | | 3(6z-1)-4(z+2)=5(z+1) | | 4d+3=8 | | 7x+4x=12 | | -9x-1=71 | | 7x+4+=12 | | 217-5x=40x+22 | | 10-7x=127-28x | | 10-7x=127-18x | | 114-5x=2x+26 | | -8x-5=19 | | 5x^2+3x=3 | | 5y-2x=10 | | 0.04(x-0.2)=-0.03(2x+0.6) | | .167x^2-.333x-1=0 | | 9x+5=2x+33 | | 25-x^2= | | 8x-2x+18=0 | | (1+7i)+(9-1)=0 | | 0.3(c+5)=0.4(1-2c) | | r^2+5=0 | | r^2+1=0 | | x/(x-3)+3=5x/(3-x) | | 2(x-0.2)=3x-1.4 |